A Method of Connecting Traditional Energy-Consuming Equipment to the Internet of Things. Issue 1 (1st November 2022) - Li, Bingchen; Xiong, Lei; Jin, Zhongwen; Wang, Jie; Tian, Haoyu
Abstract: The concept of the Internet of things affects the way that people control electrical appliances. Moreover, due to the increasing importance of energy saving, the transformation of electrical power and energy system (EPES) is urgently needed. However, massive waste of energy caused by the inappropriate use of power-consuming equipment and most of the electrical devices controlled in traditional methods. This paper illustrates an Internet of Things (IoT) and edge computing (EC) technique to intellectualize standard energy-consuming equipment via LoRa wireless technology. The proposed system is low power and supports ad-hoc networks. Each node connects to the Internet via a LoRa based gateway. We mainly focus on controlling regular air conditioning and lighting system in office buildings via web pages, apps, etc. To simplify the process of installing the purposed node, several techniques were used to take over the control of traditional power-consuming equipment via user-side. The EC node can receive the short control command and operate itself according to the environment sensing results without control intelligence from cloud server. The experimental results indicate that our intellectualized network can work reliably and save energy-consuming equipment from wasting power.